Low-Fat Dietary Pattern and Cancer Mortality in the Women's Health Initiative (WHI) Randomized Controlled Trial. Issue 4 (7th January 2019) - Chlebowski, Rowan T; Anderson, Garnet L; Manson, JoAnn E; Prentice, Ross L; Aragaki, Aaron K; Snetselaar, Linda; Beresford, Shirley A A; Kuller, Lewis H; Johnson, Karen; Lane, Dorothy; Luo, Juhua; Rohan, Thomas E; et al.
Abstract: Background: In the Women's Health Initiative Dietary Modification trial, a low-fat dietary pattern reduced deaths after breast cancer. Mortality from other cancer sites has not been reported. Methods: A low-fat dietary pattern influence on deaths from and after site-specific cancers was examined during 8.5 years (median) of dietary intervention and cumulatively during 17.7 years (median) of follow-up. A total 48 835 postmenopausal women, ages 50–79 years, were randomly assigned from 1993 to 1998 at 40 US clinical centers to dietary intervention (40%, n = 19 541 or a usual diet comparison group (60%, n = 29 294). Dietary intervention influence on mortality from protocol-specified cancers (breast, colon and rectum, endometrium and ovary), individually and as a composite, represented the primary analyses. Results: During the dietary intervention period, a reduction in deaths after breast cancer (HR = 0.65 95% CI = 0.45 to 0.94, P  = .02) was the only statistically significant cancer mortality finding. During intervention, the HRs for deaths after the protocol-specified cancer composite were 0.90 (95% CI = 0.73 to 1.10) and 0.95 (95% CI = 0.85 to 1.06) for deaths after all cancers. During 17.7 years of follow-up with 3867 deaths after all cancers, reduction in deaths after breast cancer continued in the dietary intervention group (HR = 0.85, 95% CI = 0.74 to 0.99, P  = .03). However, no dietary intervention influence on deaths from or after any other cancer or cancer composite was seen. Conclusions: A low-fat dietary pattern reduced deaths after breast cancer. No reduction in mortality from or after any other cancer or cancer composite was seen.